Bacterial Isolates from Ethiopian Soda Lake Producers of Alkaline-Active β-Glucanases Resistant to Chelating and Surfactant Compounds - Minig, Paola Marisol (2009)
β-glucanase activities were screened from isolated bacteria of the Ethiopian Shala Lake. Five isolates were selected according to the highest production of alkaline-active β-glucanase. By sequence analysis of 16S rDNA and physiological tests, four strains (SES01, SES22, SES4 and SES05) were related to Bacillus halodurans specie and the strain SES33 was identified up to genus level as Bacillus sp. Intergenic spacer regions fingerprinting showed different patterns among selected strains, having DNA amplicons of high molecular weight characteristic of alkaliphilic Bacillus. Herein, B. halodurans SES01 produced a highly stable β-glucanase in presence of surfactant and chelating compounds (sodium lauryl sulphate, Triton X-100 and EDTA) indicating its potential as additive for laundry technologies.